PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR PADA MUATAN IPAS SISWA KELAS V UPTD SD NEGERI 78 PAREPARE - Musfirah, Musfirah; Zaid Zainal; Rukmana, Riska Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is the low learning outcomes of grade V students. The problem in this study is how to apply the Project Based Learning (PjBL) learning model to improve the learning outcomes of IPAS students V UPTD SD Negeri 78 Parepare. This research is a class action research (PTK) which aims to determine the process and results of applying the Project Based Learning (PjBL) learning model for V UPTD SD Negeri 78 Parepare students on the material of the digestive system in humans. The approach used in the research is a qualitative approach. The data collection techniques used were observation, tests, and documentation. The research subjects were class teachers and students totaling 21 people consisting of 8 women and 13 men. The research was conducted in two cycles. In cycle I, the results of research on the learning process were in the sufficient qualification (C) and the percentage of completeness of the learning test results was 61.90%. In cycle II, the research results on the learning process increased to good qualifications (B) and the percentage of completeness of the learning test results was 85.71%. The conclusion of this study is that the application of the Project Based Learning (PjBL) learning model can improve the process and learning outcomes of IPAS students V UPTD SD Negeri 78 Parepare.